SWEDISH EXPLORERS, IN-SITU KNOWLEDGE, AND RESOURCE-BASED BUSINESS IN THE AGE OF EMPIRE. Issue 3 (27th May 2018) - Avango, Dag; Högselius, Per; Nilsson, David
Abstract : The period from 1870 to 1914 plays a unique role in the history of natural resource exploration and extraction. This article analyses, from a Swedish viewpoint, the connections between two actor categories of special importance in this context: scientific-geographical explorers and industrial actors. The article examines their activities in three broadly defined regions: the Arctic, Russia, and Africa. We show that the Swedes generally had far-reaching ambitions, on par with those of the large imperial powers. In some cases, notably in Africa, Sweden was not able to compete with the larger imperial powers; but in other cases, such as the exploration of the Arctic – from Spitsbergen to Siberia – and the industrial exploitation of coal at Spitsbergen and petroleum in Russia's colonial periphery, Swedish actors played a leading role, in competition with players from the larger European nations. Our paper shows that scientific exploration and industry were closely linked, and that foreign policy also influenced the shaping of these links. We distinguish different types of knowledge produced by the Swedish actors, pointing to local, situated knowledge as the most important type for many resource-based businesses, although modern, scientific knowledge was on the increase during this period.